2017
DOI: 10.1002/cepa.248
|View full text |Cite
|
Sign up to set email alerts
|

08.23: Performance and design of shear‐keys in hybid RC beam and steel column systems

Abstract: This study describes experimental and numerical investigations into the inelastic performance of hybrid structural configurations consisting of reinforced concrete (RC) beams connected to steel columns by means of fully-embedded structural steel profiles (shear-keys). Experimental observations from a series of fourteen full-scale hybrid steel/RC specimens are presented. To provide further insights into the key response characteristics, detailed numerical analyses for the tested configurations are also carried … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…For all the material and geometrical characteristics examined in the experiments, the embedded shearkey was of sufficient strength, with no local failures in the steel insert taking place at ultimate. To better understand the shear force distribution and reactions at the shear-key, parametric investigations showed that for flexural reinforcement ratios (e.g ρl=0.3%), the shear-key takes a higher amount of force than in the case of relatively high reinforcement ratios (ρl=1.1-1.9%) [26,56]. In the former case, about 80% of the total force is transferred by the shear-key, whilst it varies in the second but can be as low as 40%.…”
Section: Shear-key Designmentioning
confidence: 99%
“…For all the material and geometrical characteristics examined in the experiments, the embedded shearkey was of sufficient strength, with no local failures in the steel insert taking place at ultimate. To better understand the shear force distribution and reactions at the shear-key, parametric investigations showed that for flexural reinforcement ratios (e.g ρl=0.3%), the shear-key takes a higher amount of force than in the case of relatively high reinforcement ratios (ρl=1.1-1.9%) [26,56]. In the former case, about 80% of the total force is transferred by the shear-key, whilst it varies in the second but can be as low as 40%.…”
Section: Shear-key Designmentioning
confidence: 99%
“…To avoid previously mentioned mesh-dependency problems the crack band model with constant facture energy in which the tensile response is a function of the characteristic element length, may be considered. Models employing such approaches were able to predict the ultimate strength and deformational response of plain and reinforced concrete members (e.g., localized behavior under direct shear and tension [58,59], assessment of a long-term behavior [60], RC flat slabs with and without shear reinforcement under static loading [61][62][63], RC hybrid beams in shear and flexure [64][65][66][67]). However, detailed numerical studies on flat slabs with shear-heads are relatively limited and have typically focused on hybrid connections between steel columns and RC floors.…”
Section: Introductionmentioning
confidence: 99%